Ireland : Report on Observance of Standards and codes (ROSC). (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses findings and recommendations of the Report on Observance of Standards and codes for Ireland. The Central Bank of Ireland (CBI) is the integrated financial supervisor in Ireland. As the primary regulator of the Irish financial system, CBI has overall responsibility for the supervision of insurers and insurance intermediaries authorized in Ireland. The authorities need to address the significant challenges faced by CBI in attracting and retaining supervisors and to enhance the CBI's independence. CBI is also advised to review the supervisory risk appetite underpinning Probability Risk Impact Supervisory System, including potential reputational risks.